Development of Novel HPLC Method for Analysing Drugs Used in H-Pylori Treatment - Alfaqeer, Rawan; Albakain, Ramia; Rasheed, Mohammad; Makahleh, Ahmad (Jordan Journal of Pharmaceutical Sciences, 2021)
Helicobacter pylori (H. pylori) is the most chronic bacterial infection on human being that is found in the gastric mucous layer and adapted to survive in acidic conditions. Because of the resistance of this organism, triple therapy treatment is required. In this study, RP-HPLC method was developed in terms of mobile phase composition, buffer concentration and additive amount to separate the complex drugs mixture used as triple therapy for H. pylori treatment. The first result showed that C18 reversed phase column has better resolution than C8 for analyzing amoxicillin, metronidazole, omeprazole and clarithromycin at isocratic elution mode. Design of experiments was then implemented to evaluate the best separation parameters. The results showed that amoxicillin was detected at 254 nm, where metronidazole, omeprazole and clarithromycin were detected at 304 nm. Moreover, better resolution was achieved at mobile phase compositions of 30:30:40 (acetonitrile: methanol: buffer), respectively. Regarding the optimum amount of trimethylamine added to the mobile phase to improve the resolution, the outcomes showed that 30 µL was the best choice at pH around 6.0 with 0.05 M potassium dihydrogen phosphate as a buffer. The developed method could separate the mixture as following; amoxicillin and omeprazole at 2.56, 4.84, respectively, where metronidazole and clarithromycin were retained 3.04 min.